2021
DOI: 10.7150/jca.58500
|View full text |Cite
|
Sign up to set email alerts
|

FIN56, a novel ferroptosis inducer, triggers lysosomal membrane permeabilization in a TFEB-dependent manner in glioblastoma

Abstract: Objective: To explore the anti-tumor effect of FIN56, a novel ferroptosis inducer, on glioblastoma and its underlying mechanisms. Methods: Two human glioblastoma cell lines, LN229 and U118 were applied in this study. Anti-tumor effect was measured by CCK-8 assay, EdU assay and cell cycle analysis. Fluorescent probes, immunofluorescence, plasmid transfection, shRNA knocking out, reverse transcription PCR, western blot analysis, and transmission electron microscopy were used to study the underlying mechanisms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Interestingly, the GPX4 depletor FIN56 ( Figure 4 ) was recently shown to induce ferroptosis in in vitro and in vivo GBM models ( 105 ); this was the first study to use this compound in vivo . However, the trial was not carried out with tumors in nervous tissue but rather in nude mice with subcutaneous tumors, which makes it difficult to extrapolate the possible eventual effects of FIN56 on the brain, and it is not known whether this compound can cross the blood–brain barrier to be considered a potential therapy in the future.…”
Section: Glioblastomamentioning
confidence: 98%
“…Interestingly, the GPX4 depletor FIN56 ( Figure 4 ) was recently shown to induce ferroptosis in in vitro and in vivo GBM models ( 105 ); this was the first study to use this compound in vivo . However, the trial was not carried out with tumors in nervous tissue but rather in nude mice with subcutaneous tumors, which makes it difficult to extrapolate the possible eventual effects of FIN56 on the brain, and it is not known whether this compound can cross the blood–brain barrier to be considered a potential therapy in the future.…”
Section: Glioblastomamentioning
confidence: 98%
“…Zhang et al. reported that FIN56 can increase lysosomal membrane permeability through a tFeb-dependent pathway and thus promote glioblastoma cell death ( 144 ).…”
Section: Caspase-independent Rcd In Targeted Therapymentioning
confidence: 99%
“…Irreversibly, the traditional ferroptotic activator (1S, 3R)-RSL3 may reduce the enzymatic activity of the Gpx4 enzyme by covalently engaging its active site selenocysteine [ 18 ]. A novel ferroptosis inducer known as FIN56 is involved in reducing the amount of Gpx4 present [ 19 ]. While the precise process is still unknown, it may have something to do with the catalase activity for acetyl-CoA carboxylase [ 20 ].…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%